2022
DOI: 10.1038/s41430-022-01141-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and criteria used in the diagnosis of hospital-acquired malnutrition in adults: a systematic review and pooled incidence analysis

Abstract: Despite advances in identifying malnutrition at hospital admission, decline in nutritional status of well-nourished patients can be overlooked. The aim of this systematic review was to investigate the incidence of hospital-acquired malnutrition (HAM), diagnostic criteria and health-related outcomes. PubMed, CINAHL, Embase and Cochrane Library were searched up to July 2021. Studies were included if changes in nutritional status was assessed with a validated nutrition assessment tool in acute and subacute adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Malnutrition has negative effects on quality of life and patient outcomes, and can lead to increased healthcare costs ( 15 , 16 ). Its incidence can be as high as 12.6–52% ( 17 ), and research has shown that the incidence of hospital-acquired malnutrition can reach 25.9%, which is associated with longer hospital stays, higher readmission rates at 6 months, and may be related to higher rates of complications and infections ( 18 ). The ratio of EN/EN + PN is negatively correlated with mortality ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition has negative effects on quality of life and patient outcomes, and can lead to increased healthcare costs ( 15 , 16 ). Its incidence can be as high as 12.6–52% ( 17 ), and research has shown that the incidence of hospital-acquired malnutrition can reach 25.9%, which is associated with longer hospital stays, higher readmission rates at 6 months, and may be related to higher rates of complications and infections ( 18 ). The ratio of EN/EN + PN is negatively correlated with mortality ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Esto también provoca que exista un desperdicio de alimentos preocupante, que afecta a la economía de los hospitales y causa consecuencias medioambientales (Schiavone et al, 2019). Una estancia hospitalaria prolongada provoca que el estado nutricional del paciente se deteriore (Botero et al, 2023;Cuong et al, 2018;Rinninella et al, 2018). Sufrir de desnutrición hospitalaria provoca que la estancia hospitalaria sea mayor y viceversa, a comparación de aquellos pacientes con buenos niveles de nutrición (Behiry & Salem, 2019;Ouaijan et al, 2023;Poudineh et al, 2021;Rabeh et al, 2019;Woodward et al, 2020), además que aumenta los costos hospitalarios (Bhirommuang et al, 2019;Cheng et al, 2019;Yárnoz-Esquíroz et al, 2019).…”
Section: Factores Clínicos Y De Saludunclassified
“…Older age, low income, immobility and a long length of hospital stay can increase the risk of malnutrition (Uhl et al., 2021). It is estimated that 20%–50% of hospital inpatients are malnourished (Bellanti et al., 2022) and a quarter of long‐stay patients become malnourished during their hospital stay (Botero et al., 2023). Malnutrition is associated with an increased risk of complications, pressure injury and falls and a decline in muscle strength (Bellanti et al., 2022).…”
Section: Introductionmentioning
confidence: 99%